The Science Underlying COVID-19: Implications for the Cardiovascular System - Liu, Peter P; Blet, Alice; Smyth, David; Li, Hongliang (Circulation (New York, N.Y.), 2020)
The coronavirus disease 2019 (COVID-19) pandemic has affected health and economy worldwide on an unprecedented scale. Patients have diverse clinical outcomes, but those with preexisting cardiovascular disease, hypertension, and related conditions incur disproportionately worse outcome. The high infectivity of severe acute respiratory syndrome coronavirus 2 is in part related to new mutations in the receptor binding domain, and acquisition of a furin cleavage site in the S-spike protein. The continued viral shedding in the asymptomatic and presymptomatic individuals enhances its community transmission. The virus uses the angiotensin converting enzyme 2 receptor for internalization, aided by transmembrane protease serine 2 protease. The tissue localization of the receptors correlates with COVID-19 presenting symptoms and organ dysfunction. Virus-induced angiotensin converting enzyme 2 downregulation may attenuate its function, diminish its anti-inflammatory role, and heighten angiotensin II effects in the predisposed patients. Lymphopenia occurs early and is prognostic, potentially associated with reduction of the CD4+ and some CD8+ T cells. This leads to imbalance of the innate/acquired immune response, delayed viral clearance, and hyperstimulated macrophages and neutrophils. Appropriate type I interferon pathway activation is critical for virus attenuation and balanced immune response. Persistent immune activation in predisposed patients, such as elderly adults and those with cardiovascular risk, can lead to hemophagocytosis-like syndrome, with uncontrolled amplification of cytokine production, leading to multiorgan failure and death. In addition to the airways and lungs, the cardiovascular system is often involved in COVID-19 early, reflected in the release of highly sensitive troponin and natriuretic peptides, which are all extremely prognostic, in particular, in those showing continued rise, along with cytokines such as interleukin-6. Inflammation in the vascular system can result in diffuse microangiopathy with thrombosis. Inflammation in the myocardium can result in myocarditis, heart failure, cardiac arrhythmias, acute coronary syndrome, rapid deterioration, and sudden death. Aggressive support based on early prognostic indicators with expectant management can potentially improve recovery. Appropriate treatment for heart failure, arrhythmias, acute coronary syndrome, and thrombosis remain important. Specific evidence-based treatment strategies for COVID-19 will emerge with ongoing global collaboration on multiple approaches being evaluated. To protect the wider population, antibody testing and effective vaccine will be needed to make COVID-19 history.